The Effect of Bevacizumab on Wound Healing Modulation in an Experimental Trabeculectomy Model. (May 2014) - Ozgonul, Cem; Mumcuoglu, Tarkan; Gunal, Armagan
Abstract Purpose: Glaucoma filtration surgery remains the most effective surgical procedure for lowering intraocular pressure (IOP) in uncontrolled glaucoma. Modulation of wound healing is critical to ensure long-term surgical success. This study aimed to determine if bevacizumab is an alternative agent for wound modulation in glaucoma surgery. Materials and methods: Forty-eight eyes of New Zealand rabbits were divided into four groups undergoing standard trabeculectomy surgery in the right eye. In group 1, balanced salt solution injections (0.1 ml) were performed into the bleb. Bevacizumab (0.1 ml, 1.25 mg) was injected into the bleb in group two and into the vitreous body in group three. Subconjunctival injections of 5-fluorouracil (5-FU) were performed into the non-bleb area in group four. Postoperatively; IOP, bleb size, bleb height, bleb vascularity were evaluated. Right eyes of two animals from each group were enucleated in 10th, 20th and 30th d postoperatively and evaluated histopathologically for inflammation, neovascularization and fibrosis. Results: The length, the width and the height of the bleb in the group two were greater than other groups. Mean IOP values were lower in group two. IOP measurements in the operated eyes of group two were statistically significantly lower than the other groups until the 28th d. Inflammation (p = 0.030), neovascularization (p = 0.004) and fibrosis (p < 0.000) in group two were lower in histopathological evaluation. Conclusions: Post-operative subconjunctival injection of bevacizumab is more effective than intravitreal bevacizumab or subconjunctival 5-FU injections for bleb survival. Furthermore, IOP is lower for a long period with lower level of fibrosis, which increases the success of trabeculectomy.